"Blaming the Flowers for Wilting": Idealized Aging in a Health Charity Video. (February 2016) - Harris, Roma; Wathen, C. Nadine; MacGregor, Jennifer C. D.; Dennhardt, Silke; Naimi, Anthony; Ellis, Kathleen S.
Amid growing concern about the graying population, an emerging theme in public health discourse is that of "successful aging." In this article, we use a governmentality lens to analyze a Canadian health promotion video, titled "Make Health Last: What Will Your Last 10 Years Look Like?" and viewers' responses to its message. The video presents starkly different scenarios of the last decade of life, conveying a neo-liberal rationality in which health in old age is positioned as a matter of individual choice. Our analysis suggests that while viewers generally support the video's message of personal responsibility for health, some are uneasy about implied claims that age-related illness can be prevented by choosing to be healthy. We argue that the video's simplistic messaging about health in later life raises disturbing questions about health promotion campaigns that deny the "normal" aging body and blame the elderly for "deciding" not to remain youthful and healthy.